PENGARUH RASA, PENAMPILAN, TINGKAT KEMATANGAN, SUHU, KEBERSIHAN DAN PORSI MAKANAN TERHADAP KEPUASAN PASIEN PADA PELAYANAN GIZI DI RS X MALANG - Hariez, Tsalits Maulidah; Akbar, Prima Soultoni (Politeknik Kesehatan Kemenkes Malang (State Health Polytechnic of Malang), 2019)
Providing good quality food and the amount according to the needs and proper service for patients is the goal of organizing hospital food. nutritional service quality can also be seen from patient satisfaction with hospital facilities and services, including patient satisfaction in nutrition services. Patient satisfaction is product expectations and patient perceptions of service quality. This study aims to determine the effect of the influence of taste, appearance, maturity level, temperature, cleanliness and portion of food on patient satisfaction in nutritional services in Malang. This research design is observational analytic with cross design. This research was conducted at X Malang Hospital. The respondents of this study were 70 people. The dependent variable is the influence of taste, appearance, maturity, temperature, cleanliness and portion of food. Independent variable is patient satisfaction The results showed that patient satisfaction was influenced by the influence of taste (b = 2.41; 95% CI = 0.05 to 0.46; p = 0.016), appearance (b = 2.41; 95% CI = 0.05 to 0.46; p = 0.016), maturity level ( b = 2.41; 95% CI = 0.05 to 0.46; p = 0.016), temperature (b = 2.41; 95% CI = 0.05 to 0.46; p = 0.016) and cleanliness and portion of food (b = 2.41; 95% CI = 0.05 to 0.46; p = 0.016). Keywords: food quality, nutritional service satisfaction